Mid-term results after proximal humeral fractures following angular stable plate fixation in elderly patients—which scores can be evaluated by a telephone-based assessment? - Ziegler, Patrick (J Orthop Surg Res, 2020)
BACKGROUND: The aim was to evaluate postsurgical outcome in elderly patients (> 70 years) after open reduction and internal fixation (ORIF) of proximal humeral fractures and compare the test-retest agreement of scores which are frequently used to assess the outcome of upper extremity disorders. METHODS: Ninety patients (78.1 ± 5.2 years) with a minimum follow-up of 2 years (3.7 ± 0.9 years) following angular stable plate fixation of a proximal humeral fracture (2-part: 34, 3-part: 41, 4-part: 12) were enrolled. Two telephone-based interviews assessed Disabilities of the Arm, Shoulder and Hand Score (DASH), Oxford Shoulder Score (OSS), and Constant Score adjusted for interview assessment (CS) by two independent interviewers. Correlations, Bland-Altman analyses, Cross tabulation, and weighted Kappa measure of agreement (k) were calculated to assess differences and the test-retest agreement between the categories of each score. RESULTS: In the first and second interview, we could state fair outcomes: CS 91 (range 40–100) and 65.5 (23–86), DASH 12.5 (0–64.2) and 18.3 (0–66.7), and OSS 58 (33–60) and 55 (25–60) points. The test-retest correlations were r = 0.67, r = 0.77, and r = 0.71 for CS, DASH, and OSS. Bland-Altman analyses showed absolute mean individual score differences of − 22.3, 4.9, and − 3.0 for CS, DASH, and OSS. Limits of agreement represented possible differences of 21.6%, 15.5%, and 9.0% of CS, DASH, and OSS. The category agreements were medium to high: CS 55.9% (k = 0.08), DASH 87.2% (k = 0.62), and OSS 99.3% (k = 0.74). CONCLUSION: Patients showed good subjective outcomes. The test-retest agreement of the interview-adjusted CS was low, but telephone-based assessment of OSS and DASH present as an alternative to collect outcomes in elderly patients. TRIAL REGISTRATION: (250/2011BO2).